Pengaruh Brand Image, Kualitas Produk dan Harga Terhadap Keputusan Pembelian pada Buttonscarves Pekanbaru - Ellen Natasa; Endang Sutrisna (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Purchase Decision is one of the important aspects in marketing concepts, which serves as the background of this research. The implementation of a strong brand image, good product quality, and appropriate pricing in the eyes of consumers are the strategies applied by Buttonscarves Pekanbaru. This study aims to determine the effect of brand image, product quality, and price on purchase decisions at Buttonscarves Pekanbaru. The method used in this research is descriptive and quantitative, with data sources consisting of primary and secondary data. The sample size for this study is 100 respondents, selected using accidental sampling technique. The analytical methods used include simple and multiple regression analysis, along with validity and reliability testing. The results of this study indicate that Brand image (X1) has a positive and significant effect on Purchase Decision (Y), Product Quality (X2) has a positive and significant effect on Purchase Decision (Y), and Price (X3) has a positive and significant effect on Purchase Decision (Y). Furthermore, Brand image (X1), Product Quality (X2), and Price (X3) collectively have a positive and significant effect on Purchase Decision (Y) at Buttonscarves Pekanbaru